Comparison of absorption simulation in semiconductor nanowire and nanocone arrays with the Fourier modal method, the finite element method, and the finite-difference time-domain method. (15th December 2020) - Anttu, Nicklas; Mäntynen, Henrik; Sadi, Toufik; Matikainen, Antti; Turunen, Jari; Lipsanen, Harri
Abstract: For the design of nanostructured semiconductor solar cells and photodetectors, optics modelling can be a useful tool that reduces the need of time-consuming and costly prototyping. We compare the performance of three of the most popular numerical simulation methods for nanostructure arrays: the Fourier modal method (FMM), the finite element method (FEM) and the finite-difference time-domain (FDTD) method. The difference between the methods in computational time can be three orders of magnitude or more for a given system. The preferential method depends on the geometry of the nanostructures, the accuracy needed from the simulations, whether we are interested in the total, volume-integrated absorption or spatially resolved absorption, and whether we are interested in broadband or narrowband response. Based on our benchmarking results, we provide guidance on how to choose the method.